2002
DOI: 10.1002/hed.10111
|View full text |Cite
|
Sign up to set email alerts
|

Spindle epithelial tumor with thymus‐like differentiation (SETTLE) of the thyroid

Abstract: SETTLE of thyroid gland is an extremely rare entity. A review of the literature reveals that SETTLE has distinctive morphologic features and an immunohistochemical profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Only two cases have been reported in living children (15,16), and both were identified only after surgical excision. Malignant intrathyroidal thymic tissue, although rare, is more frequent than its benign counterpart (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), and it is known as intrathyroidal epithelial thymoma (ITET)=carcinoma showing thymus-like differentiation (CASTLE). A variant is spindle epithelial tumor with thymus-like differentiation (SETTLE).…”
Section: Discussionmentioning
confidence: 99%
“…Only two cases have been reported in living children (15,16), and both were identified only after surgical excision. Malignant intrathyroidal thymic tissue, although rare, is more frequent than its benign counterpart (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), and it is known as intrathyroidal epithelial thymoma (ITET)=carcinoma showing thymus-like differentiation (CASTLE). A variant is spindle epithelial tumor with thymus-like differentiation (SETTLE).…”
Section: Discussionmentioning
confidence: 99%
“…While most diagnoses are made at the stage when the tumor is still localized, about 20% of patients develop metastases. Metastatic relapse has been observed even many years after first diagnosis, with a mean time to relapse of 11 years [7][8][9][10]. Until now no standard treatment for metastatic SETTLE has been established due to its rarity.…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse immunoreactivity of spindle cells for epithelial markers and tonofilaments and rare well-developed desmosomes present in the spindle cells, identified by ultrastructural studies, are evidence of an epithelial nature [1,12,27,28]. In addition, Su et al [12] reported one case of SETTLE that demonstrated a myoepithelial phenotype including immunoreactivity for smooth-muscle actin and ultrastructural evidence of cytoplasmic filaments with dense bodies.…”
Section: Discussionmentioning
confidence: 99%